How to Become Technology-Based Entrepreneur - E W Anggraini; S I P Persada (Universitas Komputer Indonesia, 2021)
This study aims to describe the millennial generation to become online entrepreneurs, where the problem in this generation is a high level of consumption. Therefore, this generation must be more observant to see business opportunities in popular activities on social media, especially Instagram and utilize social networking as a market business. This research used a descriptive method and interviews to describe the ease of access to social media, the level of consumptive achievement in the millennial generation, and the widespread use of social media for the business market. The results of this study are the use of social media and more critical to see business opportunities by utilizing social networks that can meet our own needs and invest in small businesses. It can be seen from the many new business-based accounts used by Millennials on social media. It can be concluded, that social networking has the best interaction between business owners with consumers and potential customers. Besides, the smart and productive use of the internet can benefit business owners